(untitled) (Orthodontic Journal of Nepal, 2025)
Miniscrew-Assisted Rapid Palatal Expansion (MARPE) is an effective technique designed to treat maxillary transverse defiiencies, particularly in patients who are beyond their peak growth period. This case report discusses a 15-year-old male who presented with irregularly aligned upper and lower anterior teeth. He had previously undergone orthodontic treatment involving the extraction of all first premolars. The treatment plan involved maxillary expansion using a custom-fabricated MARPE appliance and supported by two temporary anchorage devices (TADs), in combination with full fixed orthodontic appliances for alignment and levelling. The treatment, completed over 18 months without further extractions, resulted in well-aligned arches, correction of the crossbite, improvement of the open bite, and enhanced facial aesthetics. This case demonstrates the successful application of MARPE as a non-surgical approach to managing complex malocclusions involving transverse and vertical discrepancies in late adolescent patients.